Sleep monitoring: a comparison between three wearable instruments. - van Wouwe NC; Valk PJ; Veenstra BJ; van Wouwe, Nelleke C; Valk, Pierre J L; Veenstra, Bertil J (Military Medicine, 2011)
During military operations soldiers often encounter extreme environmental circumstances like heat, cold, prolonged physical exercise, and disturbed sleep, which hamper their performance. Monitoring changes in physiological parameters may assist with adequate interventions to prevent the negative consequences and support recovery. The current study was employed to reduce the number of measurement instruments to monitor physiological variables, especially with respect to adequate sleep prediction. We compared three instruments with respect to their effectiveness in predicting sleep; the Equivital, Sensewear, and Actiwatch. Additionally, we investigated the added value of cardio-respiratory to accelerometer signals to estimate sleep duration. The Equivital model (based on acceleration data) and Sensewear predict sleep and wake as accurate as the commonly used Actiwatch model, and the cardio-respiratory Equivital data further improve accuracy and specificity. In sum, the current study provides an indication that the Equivital system (or any other chestband that measures 3-dimensional acceleration plus other physiological variables) might be interchanged with an Actiwatch for sleep prediction.